Effectiveness of Persea americana Mill Fruit Facial Skin Mask and Rice Flour in Inhibiting Propionibacterium acnes - Bethary, Niande Sekar; Asri, Mahanani Tri; Yakub, Pramita (LenteraBio : Berkala Ilmiah Biologi, 2025)
Skin diseases were caused by microorganisms such as Propionibacterium acnes bacteria, which triggered acne vulgaris or acne. Treating acne using antibiotics at inappropriate doses could cause resistance, so alternative natural treatments were needed. This research aimed to test the effect of a combination of avocado skin and rice flour on the growth of P. acnes, formulated as a powder mask. This experimental research used the Completely Randomized Design (CRD) method with treatment concentrations of 10%, 15%, 20%, positive control, and negative control. This research included five repetitions. Data analysis used the Kolmogorov-Smirnov Test, One Way ANOVA Test, and Duncan Test, which showed that the data were normally distributed, all combination treatments of avocado peel powder and rice flour affected inhibiting P. acnes bacteria, and each treatment was significantly different. A 10% concentration produced an average clear zone of 6.35 ± 0.48 mm, 15% produced 8.00 ± 0.68 mm, and the most optimal concentration, a 20% concentration, produced 11.05 ± 0.37 mm. Thus, it was proven that combining avocado skin powder and rice flour inhibited P. acnes bacteria and could be used as an alternative natural acne treatment.